Use of pitanga extract in the control of phytopathogenic fungus in Adenium obesum (Research, Society and Development, 2022)
The use of chemical control is not always feasible or appropriate in certain types of production, so it seeks the development of technologies that can be used in an alternative way to plant disease control. This study aims to verify the efficiency of the aqueous extract of pitangueira leaves at different concentrations in the control of phytopathogenic fungus in Desert Rose. The experiment was developed in vitro at the Phytopathology Laboratory of the Federal University of Maranhão. The fungus was isolated indirectly from the leaves of desert rose plants with subsequent peaking for purification of the colony in Petri dishes using BDA. After six days of incubation, the colonies received individually within the Petri dishes a paper of about 1 cm in diameter previously immersed in aqueous extract solutions of pitangueira leaves. The extract was made in a concentration of 150g of leaves for 1 L of ADE, to obtain the same pitangueira leaves were dried and crushed, then dipped in ADE where they stayed for 8 days suffering slight daily agitation. For application the extract was diluted at concentrations of 0%, 5%, 10% and 15%. The Mycelial Growth Index (MCI) was evaluated from the first day on which the control was applied, with a time of 24 h between each evaluation. It was concluded that the aqueous extract of pitangueira leaves has no inhibiting power over the mycelial growth of this fungus.